Seleção de genótipos de Artemisia annua L. com base em caracteres agronômicos, fisiológicos e fitoquímicos - Dallacorte, Lucas Vinicius (2022)
Artemisia annua L. is the only commercial source of artemisinin, the main compound used to treat malaria. This project was developed with the objective to select superior plants of A. annua within the open pollination cultivar CPQBA-3, using agronomic, phytochemical and physiological characters. The project was developed in the experimental area of the UTFPR of Pato Branco – PR, in the years 2019-2020 and 2020-2021. The preparation of the seedlings took place in a greenhouse under extended artificial photoperiod (+ 6 hours) to prevent flowering. The field planting took place in October when the seedlings were about 0.2 m. The harvesting of the plants took place in the month of March. In the harvest were measured agronomic characters; dry mass of leaves and branches, diameter of the lower, median and upper sections of the canopy and the main branch of the plants, height of the plant and insertion of the first pair of plagiotropic branches, total number of branches and total biomass of the aerial part. Physiological characteristics measured were net CO2 assimilation, internal CO2 concentration, respiration rate, stomatal conductance and water use efficiency. Subsequently, phytochemical evaluations were performed to quantify the content of essential oil and artemisinin. Data analysis was performed by the methodology REML/BLUP and correlation between characters. Dry mass of leaves and total number of branches were those that presented the highest values of heritability in both years evaluated (0.6 and 0.78, respectively, in 2020 and 0.53 and 0.66, respectively, in 2021). The essential oil content in the plant presented a low value of heritability in both years evaluated (0.14 and 0.01), while the yield of the essential oil presented a high value of heritability in the first year (0.55). Artemisinin showed a low heritability value for the content (0.06). The content of artemisinin and essential oil showed a negative correlation with the dry mass of leaves in the plants. The maximum content observed for essential oil was 1.87 g 100 g-1 MSF in 2020 and 1.3 g 100 g-1 MSF in 2021. Regarding the artemisinin content evaluated only in the second year, the maximum value obtained was 1.67 g 100 g-1 MSF. The analysis by the BLUP methodology estimated gains for the agronomic characteristics of dry mass of leaves and total number of branches. For the phytochemical characteristics of essential oil and artemisinin content, the estimated values were close to the general average and below the observed maximum values.